(untitled) - Bird, J. O. (New York, 2015)
This book introduces mechanical principles and technology through examples and applications, enabling students to develop a sound understanding of both engineering principles and their use in practice. These theoretical concepts are supported by 400 fully worked problems, 700 further problems with answers, and 300 multiple-choice questions, all of which add up to give the reader a firm grounding on each topic.
Keywords: Kỹ sư cơ khí,Mechanical engineering; Câu hỏi, bài tập, vv,Problems, exercises, etc